Management of bleeding in patients using antithrombotic agents - Scharf, R. E. (Hämostaseologie, 2009)
Antiplatelet agents and anticoagulants are effective in the prevention and treatment of a variety of thrombotic disorders. Several clinical settings require more intense antithrombotic regimens. These can be provided by combining (i) two antiplatelet drugs, (ii) anti-platelet monotherapy with an anticoagulant, or (iii) anticoagulation with dual antiplatelet treatment (triple therapy). A major side effect of all antithrombotic regimens, however, is the induction of a bleeding diathesis. This is especially true in patients with preexisting haemostatic defects of any kind that may remain compensated, unless platelet function and/or coagulation are not inhibited pharmacologically. To address the dilemma of the “double-edged sword” between thrombosis and bleeding, several strategies are currently under study, including (i) identification of high-risk patients, (ii) stratification of patient subgroups, (iii) individualized decision making, and (iv) administration of “tailor-made” risk-adapted regimens. Nonetheless, prevention and protection from bleeding in patients using antithrombotic agents remain an enduring challenge. For high-risk patients on antiplatelet agents with urgent need of surgery, an algorithm is discussed that allows short-term interruption of oral antithrombotic therapy and i.v. administration of a GPIIb-IIIa receptor antagonist for bridging without increasing peri-operative bleeding. When individual patients, using antiplatelet or anticoagulant agents, experience serious or even life-threatening haemorrhages, haemotherapy with platelet units or prothrombin complex concentrates remains an integral part of the clinical management.
Keywords: Antiplatelet drugs; vitamin K antagonists; haemostasis monitoring; clinical trials; platelet transfusions; coagulation factor concentrates